Proposta metodológica para gestão de secas: o caso da bacia do Alto Jaguaribe, Ceará - Rêgo, Thereza Christina Citó César (2008)
The technological evolution and the robustness of the climatic forecast models give precocious impulse to alert and prevent the extreme events. Using the climatic scene constructed to 2001 - 2025 period by ECHAM4 model (ROECKNER et al., 1996), the most critical year in terms of water supply is selected using some droughts monitoring indexes and the water stress index (ARAÚJO et al., 2004). The water demands by categories of users are gotten in two scenes of regional development A and B, by Northeast Water Use Model - NoWUM (DÖLL et al., 2002). A drought management methodology is proposed to the alto Jaguaribe river region, Ceará. This methodology contemplates new management structure, relates activities to be developed, suggests measures for water use control (offers and demands) and compares its performance with the classic politics nowadays adopted. A droughts management quality indicator – IGS is determined which relates the sustainable index - IS (ASCE, 1998); water stress index - ig90 (ARAÚJO et al., 2004); access index - iAC and consumption index - iC, to populations supplied by mobile system of water distribution; municipality institutional quality indicator - IQIM (BRAZIL, 2005) and the emergency water supply costs - CE. The results point an up grade in the IGS by the new methodology. The municipalities with the worst IGS are Acopiara, Tauá e Nova Olinda. The beest ones are Quixelô, Iguatu e Arneiroz.